Design buck converter with variable switching frequency by using matlab simulink simulation - Norazila Binti Md Posdzi; Norsa’adah Binti Mahmor; Rasidah Binti Abdul Rani (International Journal of Technology, Innovation and Humanities, 2020)
This paper presents the design of a buck converter circuit with different input switching frequency by using Matlab Simulink software. This study focuses on defining the suitable value of the inductor and capacitor to be used in the buck converter with 100VDC supply input, where the input switching frequency is use 5kHz and 25kHz. This is because the input switching frequency of a buck converter affects many aspects of circuit functionality. This design of the circuit used 20% of the duty cycle, and inductor value is 25% of Lmin to ensure the operation is in continuous current mode. The evaluation of inductor current and switching frequency used in the circuit and parameters for this analysis based on the output voltage, inductor voltage and inductor current waveform. The design of the circuit verified by simulation and results compared with the theoretical. In addition, the appropriate input switching frequency between 5kHz and 25kHz has been determined in order to use in the buck converter circuit for 100Ω resistive load.